Pelanggaran Nilai Kemanusiaan Terhadap Wanita Dalam Konflik Bersenjata Di Suriah Menurut Perspektif Islam - Rifda Quthrun Nada Grandis; Rizkika Dwi Amalia (ADALAH, 2021)
International humanitarian law is compatible with the islamic law that upholds the principle of peace, because it seeks to eliminate violence. The conflict in Syria is a conflict between government and non-civilians seeking to overthrow Bashar Al-Assad's governance. Bashar Al-Assad's administration through its security forces carried out violence against civilians, especially with women exploitation and children, sexual violence, rape and so on. The method used is a descriptive qualitative method where the data obtained uses the type of data collection which is a library study of various literature such as journals and books. This research concluded that islamic law as well as international humanitarian law has the solution of conflict based on the humanitarian principles on war victims